PENGARUH FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BEI - Ria Lusiana; Shieren Novelinda; Imroatus Sholekah; Rafli Aldi Saputra (CV. Denasya Smart Publisher, 2024)
There have been many challenges in cigarette companies in recent years, including a decline in sales due to COVID-19, as well as government policies regarding excise and taxes which have triggered profit management in companies. The aim of this research is to find out how company size and financial difficulties affect earnings management. This research method uses quantitative methods with multiple linear regression analysis. The results of the analysis showed that there were symptoms of multicollinearity and autocorrelation in the regression model, but no symptoms of heteroscedasticity were found. The conclusion of this research is that financial distress and company size have an influence on earnings management of cigarette sub-sector companies on the IDX. The independent variable does not have a significant effect on the dependent variable when viewed partially, but has an effect simultaneously. Suggestions for further research are to expand the scope of the variables studied.